Social innovation education: towards a framework for learning design. Issue 4 (9th November 2015) - Alden Rivers, Bethany; Armellini, Alejandro; Maxwell, Rachel; Allen, Sue; Durkin, Chris
Abstract : Purpose: – The purpose of this paper is to propose a theoretical framework to support the embedding of social innovation education in existing academic programmes. Design/methodology/approach: – By adopting Conole et al. 's (2004) methodological approach to reviewing, mapping and modelling learning theory, this study addresses four research questions: how can social innovation education be defined? Which learning theories best support social innovation education? How do such learning theories relate to existing models of learning in higher education? What implications does a social innovation pedagogy have for learning design? Findings: – Findings suggest that social innovation education is supported by a praxis that is grounded in critical learning theory, transformational learning theory and epistemological development. By extending Conole et al. 's (2004) model of learning theory, the present study proposes a "zone of pedagogical praxis for social innovation education" that supports learning design on a more critical plane. Research limitations/implications: – The proposed model of learning may be of interest to other universities as they work towards stronger thinkers and stronger communities. Practical implications: – Using a theory-informed model for learning design nurtures a pedagogical praxis and underpins the development of a practical toolkit for designing social innovation education. Originality/value: – The findings of this study will provide a point of reference for other higher education institutions as they look for guidance on embedding principles of social innovation into their curricula.